1992
DOI: 10.1104/pp.98.2.516
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Photosynthetic Rate of Two Sunflower Hybrids under Water Stress

Abstract: The effect of short-term water stress on photosynthesis of two sunflower hybrids (Helianthus annuus L. cv Sungro-380 and cv , differing in productivity under field conditions, was measured. The rate of CO2 assimilation of young, mature leaves of SH-3622 under well-watered conditions was approximately 30% greater than that of Sungro-380 in bright light and elevated C02; the carboxylation efficiency was also larger. Growth at large photon flux increased assimilation rates of both hybrids. The changes in leaf com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
83
0
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(98 citation statements)
references
References 26 publications
9
83
0
6
Order By: Relevance
“…This is in accordance with the decrease in the quantum yield of PSII photochemistry observed in NI, allowing the adjustment of electron flow to the limited carbon uptake as a result of stomatal closure. This could also be related to the high sensitivity of photophosphorylation to leaf water deficit as reported by Giménez et al (1992). However, Rubisco activity seems to be more resistant to water stress than photophosphorylation, with significant effects occurring only for severe drought.…”
Section: Discussionmentioning
confidence: 89%
“…This is in accordance with the decrease in the quantum yield of PSII photochemistry observed in NI, allowing the adjustment of electron flow to the limited carbon uptake as a result of stomatal closure. This could also be related to the high sensitivity of photophosphorylation to leaf water deficit as reported by Giménez et al (1992). However, Rubisco activity seems to be more resistant to water stress than photophosphorylation, with significant effects occurring only for severe drought.…”
Section: Discussionmentioning
confidence: 89%
“…Although measurements of leaf photosynthesis rate have been shown to be reliable in distinguishing between drought tolerant and susceptible genotypes of some species such as sunflower (Gimenez et al, 1992), gas exchange techniques of assessing photosynthesis are laborious and not practical in crop improvement programs (Earl and Tollenaar, 1999). Rong-hua et al (2006), working with barley, showed that indirect and faster methods of measuring photosynthetic activity, such as chlorophyll a fluorescence technique, particularly the maximum photochemical efficiency of photosystem II -PSII (which can be assessed via the variable-to-maximum chlorophyll a fluorescence ratio, F v / F m ) and estimated chlorophyll content (SPAD index), can be as effective as the more time-consuming gas exchange techniques in revealing differences between drought tolerant and susceptible genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The severe impact of Cu on wheat leaf water use efficiency, as determined by the ratio between leaf photosynthesis and transpiration (AI E) and the ratio between leaf photosynthesis and stomatal conductance (AI gs), indicates the reduced control over water loss. As observed in the are plants, lower stomatal conductances were reported in many other species in severe stress environments (Lawlor and Mitchell 1991;Gimenez et al 1992;Lidon et al 1993).…”
Section: Discussionmentioning
confidence: 76%
“…Photosynthetic CO 2 assimilation per unit area of leaf surface depends on the capacity of the plant's photosynthetic mechanism and on environmental factors, such as excess Cu, which are necessary for the process. The rate of photosynthesis, in combiriation with the leaf area, determines the plant productivity (Gimenez et al 1992). Assimilation also varies in response to environmental factors.…”
mentioning
confidence: 99%